2011
DOI: 10.21273/hortsci.46.4.616
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Regeneration and Genetic Transformation of Cucumis metuliferus through Cotyledon Organogenesis

Abstract: This study was undertaken to establish for the first time an efficient regeneration and transformation system for Cucumis metuliferus line PI292190, which is the source of a well-defined resistant gene, Wmv, that provides resistance against Papaya ringspot virus type P (PRSV-P) and PRSV-W (formerly known as Watermelon mosaic virus 1, WMV-1). Different combinations of growth regulators were evaluated for the regeneration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
1
5
0
1
Order By: Relevance
“…Thus molecular basis of PRSV resistance in C. metuliferus could be elucidated by silencing representatives of candidate genes isolated in this study. A transformation system for resistant line PI 292190 has been developed successfully in our lab [64] and should facilitate understanding the resistance mechanism of C. metuliferus against PRSV in the near future through the RNAi approach. Currently, we have obtained transgenic plants harboring RNAi construct of ku2005-412 that show the breaking down the immune response of resistant line PI 292190 successfully.…”
Section: Discussionmentioning
confidence: 99%
“…Thus molecular basis of PRSV resistance in C. metuliferus could be elucidated by silencing representatives of candidate genes isolated in this study. A transformation system for resistant line PI 292190 has been developed successfully in our lab [64] and should facilitate understanding the resistance mechanism of C. metuliferus against PRSV in the near future through the RNAi approach. Currently, we have obtained transgenic plants harboring RNAi construct of ku2005-412 that show the breaking down the immune response of resistant line PI 292190 successfully.…”
Section: Discussionmentioning
confidence: 99%
“…Transformation of C. metuliferus resistant line PI 292190 was conducted according to a previously described protocol [ 26 ]. In brief, cotyledon explants of the resistant line PI 292190 were infected with A. tumefaciens strain LBA4404 harboring the CmSPI RNAi binary vector construct.…”
Section: Methodsmentioning
confidence: 99%
“…Until now, Agrobacterium-mediated transformation methods using cotyledons as explants has been the most successful approach for cucumber transformation 21 . With this approach, the transformation frequency is dependent on several factors, including plant genotype, explant source and size, Agrobacterium strains and concentration, length of exposure to Agrobacterium, and selection system 22,23 , among others. It was reported that dissecting half of an adaxial cotyledon using a V-shaped cut resulted in a higher transformation rate 24 , while another report showed that using cotyledon nodes as explants resulted in regeneration at the junction of cotyledon and hypocotyl in the proximal regions of the cotyledons 12 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, we have produced more than 600 transgenic lines and functionally analyzed a range of cucumber genes using this protocol [25][26][27][28][29][30][31][32][33] . The method can be widely used in cucumber breeding, variety improvement, and the characterization of gene function, and can be a reference for the transformation of other cucurbits, such as Cucumis melo and C.metuliferus 21,23 .…”
Section: Introductionmentioning
confidence: 99%